2015
DOI: 10.1128/aac.01779-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Molecular Events Linking to Cell Death Induced by Tetracycline in the Amitochondriate Protozoan Trichomonas vaginalis

Abstract: f Trichomonas vaginalis colonizes the human urogenital tract and causes trichomoniasis, the most common nonviral sexually transmitted disease. Currently, 5-nitroimidazoles are the only recommended drugs for treating trichomoniasis. However, increased resistance of the parasite to 5-nitroimidazoles has emerged as a highly problematic public health issue. Hence, it is essential to identify alternative chemotherapeutic agents against refractory trichomoniasis. Tetracycline (TET) is a broad-spectrum antibiotic wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Comparative bioinformatics examinations in Trichomonas vagina and Giardia intestinalis have shown the existence of the nuclease, NM23 gene family homologs, which has been implicated in DNA fragmentation. The in-depth transcriptomic signatures in Tetracycline (TET) treated-T. vaginalis showed the involvement of hydrogenosome in programmed cell death [25]. In response to beta-Lapachone treatment and starvation, Giardia lamblia presented some autophagic-like (myelinic figures in large vacuoles and LC-3 staining) and apoptotic-like (Cell shrinkage, chromatin condensation, membrane blebbing and vacuolization) programmed cell death characteristics suggesting the possible role of mitosomes, a relic organelle in these processes [26].…”
Section: Organelles Of Mitochondrial Originmentioning
confidence: 99%
“…Comparative bioinformatics examinations in Trichomonas vagina and Giardia intestinalis have shown the existence of the nuclease, NM23 gene family homologs, which has been implicated in DNA fragmentation. The in-depth transcriptomic signatures in Tetracycline (TET) treated-T. vaginalis showed the involvement of hydrogenosome in programmed cell death [25]. In response to beta-Lapachone treatment and starvation, Giardia lamblia presented some autophagic-like (myelinic figures in large vacuoles and LC-3 staining) and apoptotic-like (Cell shrinkage, chromatin condensation, membrane blebbing and vacuolization) programmed cell death characteristics suggesting the possible role of mitosomes, a relic organelle in these processes [26].…”
Section: Organelles Of Mitochondrial Originmentioning
confidence: 99%
“…degradation of cytoplasmatic components, hydrogenosome shape changes, plasmatic membrane projections (blebs), flagellar internalization, release of lysosomal enzyme, cell shape changes, cytoplasm vacuolization, photosensitizing (PS) externalization, and caspase activation [4,25,[28][29][30][31][32][33][34][35]. In the present study, T. foetus treated with PDT associated with photosensitizer tetrasulfonated aluminium phthalocyanine (AlPcS 4 ) showed "ladder-patterned" DNA fragments, in conventional electrophoresis assay and longer tails in Comet Assay.…”
Section: Introductionmentioning
confidence: 53%
“…Recent studies showed that alterations in lysosomes and hydrogenosomes were also observed in T. foetus after proteossome inhibitors treatment [24]. Other studies suggest that tetracycline disrupts hydrogenosomal function since it reduced the hydrogenosomal energy metabolism efficiency in T. vaginalis [25].…”
Section: Trichomonad Hydrogenosomesmentioning
confidence: 99%
“…However, taxol and nocodazole induced the formation of multinucleated cells, abnormal distribution of the nuclear contents and, sometimes, nuclear fragmentation [22]. In recent studies utilizing tetracycline, it was observed DNA fragmentation in T. vaginalis [25].…”
Section: Nuclear Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation